Correlation of gut microbiota with serum inflammatory index and 25-hydroxyvitamin D level in malnourished children - ZHENG Jinlu, WANG Jingjing, LI Haiqing, CHEN Xiangjian (Zhongguo linchuang yanjiu)
Objective To investigate the status of intestinal flora in malnourished children and its relationship with se.rum inflammatory cytokines and 25-hydroxyvitamin D［25 (OH) D］levels. Methods A total of 126 malnourished children admitted to Ningde Affiliated Hospital from January 2022 to August 2023 were selected as the study group. Additionally, 133 healthy children undergoing check.ups at the same hospital during the same period were selected as the control group. The clinical data of all study subjects were collected. Colony forming unit (CFU) counting method was used to count the total number of Enterococcus, Escherichia coli, Lactobacillus, and Bifidobacterium in the feces of the research subjects, and their logarithmic value were recorded. Enzyme.linked immunosorbent assay (ELISA) was used to measure serum levels of tumor necrosis factor-α (TNF-α) , C.reactive protein (CRP) , interleukin-6 (IL-6) , and 25 (OH) D. Pearson correlation analysis was employed to analyze the correlation between CRP, IL-6, TNF-α, 25 (OH) D, and gut microbiota. Results Children in the study group had lower body mass index (BMI) and a higher incidence of gastrointestinal diseases compared to the control group (P＜0.05) . Compared to the control group, the study group showed higher counts of Clostridium and Escherichia coli, lower counts of Bifidobacterium and Lactobacillus, higher levels of TNF-α, CRP, IL-6, and significantly lower serum 25 (OH) D levels (P＜0.05) . Pearson correlation analysis indicated that Escherichia coli and Clostridium in malnourished children were positively correlated with TNF-α, CRP, IL-6 levels, and negatively correlated with 25 (OH) D levels, respectively (P＜0.05) . Bifidobacterium and Lactobacillus were negatively correlated with TNF-α, CRP, IL-6 levels, and positively correlated with 25 (OH) D levels, respectively (P＜ 0.05). Conclusion CRP, IL-6, TNF-α, and serum 25 (OH) D levels are closely associated with Clostridium, Escherichia coli, Bifidobacterium and Lactobacillus in malnourished children.